2023
DOI: 10.1111/idh.12771
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of usefulness and reliability of YouTube™ videos on denture care

Nesa Aurlene,
Sabiha Shaheen Shaik,
Virginia Dickson‐Swift
et al.

Abstract: IntroductionThe world's population is in a demographic transition with a rising ageing population. Tooth loss is frequent among older people resulting in the replacement of natural teeth using complete or partial dentures. YouTube™ is the second most popular website in the world and is being increasingly used to access health care information. The aim of this study is to evaluate the usefulness and reliability of the information in YouTube™ videos regarding denture care.MethodsThe YouTube™ website was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There are studies in the literature examining the quality and reliability of YouTube™ videos in medicine and dentistry [22][23][24]. According to our literature review, this is the first study to analyze videos uploaded on YouTube™ on oral health in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in the literature examining the quality and reliability of YouTube™ videos in medicine and dentistry [22][23][24]. According to our literature review, this is the first study to analyze videos uploaded on YouTube™ on oral health in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[5,7] However, studies have shown that the content of YouTube videos about health is not high in terms of scientific quality and reliability. [9][10][11] The current study evaluated the quality, credibility, and engagement of YouTube videos about cancer and nutrition. The mean mDISCERN score was 1.96±1.13 (poor quality), JAMA score was 1.65±1.89 (fair-poor quality), GQS score was 2.25±0.95 (fair quality).…”
Section: Discussionmentioning
confidence: 99%